Limited liability of provider services for content shared in virtual space - Humbatov, Elnur Akif (Journal of the Belarusian State University. Law, 2024)
Content shared in virtual space is not always pleasant. In many cases, insults and slander, personal life information, commercial disclosures are allowed through such contents. In cases of such violations, solving the issue of responsibility of Internet providers and determining the limits of such responsibility is of great importance. In the article, the limits of providers’ responsibility are based on their classification. In this regard, the experience of foreign countries was reviewed, and German legal regulations were identified as more successful experience. Different classification of providers in Azerbaijan was assessed by the author as a shortcoming and suggestions were presented in this regard. In addition, the sequence and duration of the procedures for the removal and blocking of shared illegal content were analysed, which, depending on the type of Internet providers, is important in determining the limits of their responsibility. For this purpose, the national material and procedural legal norms were analysed, and the shortcomings of the national legislation in this field were determined, since the issue of the responsibility of the providers is related to the information whose distribution is restricted. In the end, it was concluded that making changes in the norms of responsibility for the removal of illegal content will also eliminate procedural deficiencies.